(untitled) (Research, Society and Development, 2022)
The article aims to contribute from the perspective of Early Childhood Physical Education in the transition stage of the Curricular Bases of Early Childhood Education (BCED, 2018), a level that today presents learning objectives to be developed in a specific nucleus called: Corporality and Movement, where contents of motor work from 0 to 5 years are delivered, but without a pedagogical reflection on how to carry them out. From a methodological perspective, a qualitative descriptive work with narrative and bibliographic analysis is developed, in which ministerial documents of the study are consulted, as well as articles, books and magazines associated with the subject. Faced with the results, it is necessary to contribute from the point of view of Early Childhood Physical Education for this nucleus with the explanation of how each learning objective would be approached and develop motor proposals to comply as requested in the BCEP. For this, a motor proposal was generated where the motor contents are specified from a bodily perspective, of the game and movement, implementing each conceptual and procedural content according to the ages of the transition level, which was developed after a long bibliographic review. Therefore, it is recognized the importance of providing a pedagogical tool for all those educators or teachers who will develop this nucleus through the corporality of each boy and girl present in their classrooms, but with theoretical support to impact accurate and comprehensive in child development.